NURCHOLISH MADJID ON INDONESIAN ISLAMIC EDUCATION: A HERMENEUTICAL STUDY - Safitri, Lis; Manshur, Fadlil Munawwar; Thoyyar, Husni (Islam Futura, 2022)
Indonesian Muslims need a well-established Islamic education that can accommodate diversity as the characteristic of Indonesia. Nurcholish Madjid (1939-2005), a neo-Modernist, has an inclusive and philosophical Islamic thought that can be used as the philosophical paradigm of Indonesian Islamic education. This study intends to interpret the thinking of Nurcholish Madjid related to Islamic education using Hans Georg Gadamer’s hermeneutic model. This study shows that knowledge is a manifestation of ‘aql, one of human potential as khalīfah. Cak Nur’s objective of Islamic education is divided into four categories that led to the awareness of human existence as God’s servant and khalīfah. The model of Cak Nur’s education is humanistic education which focuses on moral education. The multicultural education of Cak Nur, which comes from the generic meaning of Islam, is tolerance education to the diversity of religions, religious understanding, and the acceptance of local wisdom. Cak Nur's educational thinking is not a practical theory, but a philosophical foundation that is easily accepted by people with the epistemology of burhānī thought.